Some reflections on the correspondence between Jan Čep and Henri Pourrat - Zatloukal, Jan (Romanica Olomucensia, 2014)
Jan Čep, translator of Gaspard from the Mountains, belonged among the important non-French correspondents of Henri Pourrat. Their mutual correspondence (1932-1958), which reflects notable moments of European history of the twentieth century, is an important source not only for the literary historian. Based on this correspondence, the paper analyzes three aspects of literary reflection: how the two letter writers comment on the literary production of the time (letter as a document); how the writer critically reflects his own work (letter as a critical space); what is the relation of the correspondence and the literary création (letter as a piece of writing).
Keywords: Jan Čep; Henri Pourrat; correspondence; literary production; work in progres.